As for the Question of the Relationship Between the Concepts of «Security» and «Transport Security» - Ryazanov, Nikita S. (Sibirskoe ûridičeskoe obozrenie (Online), 2017)
This article examines the problems of determining transport security, the correlation of this category with a generic notion of security and its other types. This paper examines the formation and development of modern legislative model for transport security. Threats to the safe and sustainable functioning of the transport complex are indicated by their types are also analyzed. In addition, the Author explores the terms «transport security» and «transport safety», which, despite the similarity of language, are the different contents in the regulations, and, consequently, definition. On the results of the analysis of national legislation, the problems of legal regulation of transportation security pointed out are pointed out and suggestions are made on ways to minimize these problems. According to the results of the research, the Author develops a unified definition of transport security and its object, which is relevant today.